Application of 2-chloro-6-methoxyresorcinol in inhibition of mycobacterium tuberculosis tyrosine phosphatase A - CHEN BIN; LIU LAN; CHEN DONGNI; LU YONGJUN (2021)
The invention belongs to the technical field of medicinal chemistry, and particularly relates to application of 2-chloro-6-methoxyresorcinol in inhibition of mycobacterium tuberculosis tyrosine phosphatase A. The invention further relates to a preparation method of the 2-chloro-6-methoxyresorcinol. In order to develop a novel anti-tuberculosis drug, the invention provides a novel application of the compound 2-chloro-6-methoxyresorcinol. The compound has remarkable inhibitory activity on mycobacterium tuberculosis tyrosine phosphatase A, and is relatively low in cytotoxicity. The compound can be developed into a novel anti-tuberculosis drug taking MptpA as an action target, and can be prepared into a mycobacterium tuberculosis tyrosine phosphatase inhibitor or an anti-tuberculosis drug, so that a new direction is provided for the treatment of tuberculosis. 本发明属于药物化学技术领域，具体涉及2-氯-6-甲氧基间苯二酚在抑制结核分枝杆菌酪氨酸磷酸酶A中的用途，为开发新型抗结核药物，本发明提供了化合物2-氯-6-甲氧基间苯二酚的新用途，该化合物对结核分枝杆菌酪氨酸磷酸酶A具有显著的抑制活性，且细胞毒性较低，可开发为以MptpA为作用靶点的新型抗结核药物，制备成结核分